Informacijsko vedenje: modeli in koncepti - Vilar, Polona (Knjižnica, 2005)
The article presents an overview of the research area of information behaviour. Information behaviour is defined as the behaviour of individuals in relation to information sources and channels, which results as a consequence of their information need, and encompasses passive and active searching of information, and its use. Theoretical foundations are presented, as well as some fundamental conceptual models of information behaviour and related concepts: information searching behaviour, which occurrs in active, purposeful searching for information, regardless of the information source used; and information seeking behaviour, which represents a micro-level of information searching behaviour, and is expressed by those individuals who interact with information retrieval systems.
Keywords: informacijski viri; iskanje informacij; uporabniki; informacijsko vedenje